The ethanol extract of Aquilariae Lignum ameliorates hippocampal oxidative stress in a repeated restraint stress mouse model - Hyun-Yong Lee; Jin-Seok Lee; Hyeong-Geug Kim; Won-Yong Kim; Seung-Bae Lee; Yung-Hyun Choi; Chang-Gue Son (BMC, 2017)
Abstract Background Chronic stress contributes to the development of brain disorders, such as neurodegenerative and psychiatric diseases. Oxidative damage is well known as a causative factor for pathogenic process in brain tissues. The aim of this study is to evaluate the neuroprotective effect of a 30% ethanol extract of Aquilariae Lignum (ALE) in repeated stress-induced hippocampal oxidative injury. Methods Fifty BALB/c male mice (12 weeks old) were randomly divided into five groups (n = 10). For 11 consecutive days, each group was orally administered with distilled water, ALE (20 or 80 mg/kg) or N-acetylcysteine (NAC; 100 mg/kg), and then all mice (except unstressed group) were subjected to restraint stress for 6 h. On the final day, brain tissues and sera were isolated, and stress hormones and hippocampal oxidative alterations were examined. We also treated lipopolysaccharide (LPS, 1 μg/mL)-stimulated BV2 microglial cells with ALE (1 and 5 μg/mL) or NAC (10 μM) to investigate the pharmacological mechanism. Results Restraint stress considerably increased the serum levels of corticosterone and adrenaline and the hippocampal levels of reactive oxygen species (ROS), nitric oxide (NO), and malondialdehyde (MDA). ALE administration significantly attenuated the above abnormalities. ALE also significantly normalized the stress-induced activation of astrocytes and microglial cells in the hippocampus as well as the elevation of pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β). The in vitro assay outcome supplemented ALE could dramatically block NF-κB activation in microglia. The anti-oxidative stress effects of ALE were supported by the results of antioxidant components, 4-hydroxynonenal (4-HNE), NADPH oxidase 2 (NOX2), inducible nitric oxide synthase (iNOS) and NFE2L2 (Nrf2) in the hippocampal tissues. Conclusions We firstly demonstrated the neuroprotective potentials of A. Lignum against hippocampal oxidative injury in repeated restraint stress. The corresponding mechanisms might involve modulations in the release of ROS, pro-inflammatory cytokines and stress hormones.